(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article provides a comprehensive analysis of the grammatical nature of proper nouns from morphological, lexico-grammatical, and syntactic perspectives. It examines the word-formation models of proper nouns, orthographic norms related to capitalization, and their grammatical differentiation as personal names, place names, and institutional names. Particular attention is paid to the interaction of proper nouns with the categories of number, case, and possession. At the syntactic level, the study analyzes the functions of proper nouns as sentence constituents, their use in attributive constructions, and the emergence of generalized meanings. On this basis, the systemic integrity and functional significance of proper nouns within the language system are substantiated.